EKSISTENSI LAFAL-LAFAL AL-MUARRAB DALAM PEMBELAJARAN AL-QUR’AN - Nirmala Khoir; fitriah fitriah (al-Iltizam: Jurnal Pendidikan Agama Islam, 2021)
This journal discusses the existence of al-muarrab pronunciations in learning the Qur'an from the historical, and linguistic aspects. In learning the Qur'an there is material about the vocabulary/mufrodat of the Qur'an in which there are foreign vocabularies or al-muarrab pronunciations. This vocabulary does not reduce the miracle of the Qur'an in terms of language, in fact the presence of absorption elements in it shows that the Qur'an accommodates other languages. The main factor in the existence of foreign languages in the Qur'an is because the Arabs interacted with foreign nations in pre-Islamic times through prolonged trade routes in historical records. This led to the borrowing of foreign languages which were then used by the Arabs at that time. Of course, through a long historical process naturally through a stage called arabization or language neutralization by adjusting Arabic spoken and what the Arabs wanted. This research is a qualitative research with the nature of library research so that after collecting data, researchers carry out data processing activities, which include data classification, verification, merging, and sorting data with the aim of preparing materials for data analysis activities using content analysis.